Antitussives and substance abuse - Burns JM; Boyer EW (Dove Medical Press, 2013)
Jarrett M Burns, Edward W Boyer Division of Medical Toxicology, Department of Emergency Medicine, University of Massachusetts Medical School, Worcester, MA, USA Abstract: Abuse of antitussive preparations is a continuing problem in the United States and throughout the world. Illicit, exploratory, or recreational use of dextromethorphan and codeine/promethazine cough syrups is widely described. This review describes the pharmacology, clinical effects, and management of toxicity from commonly abused antitussive formulations. Keywords: dextromethorphan, purple drank, sizzurp, codeine/promethazine